2006
DOI: 10.1007/s10750-006-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patterns of spatial autocorrelation of assemblages of benthic invertebrates in upland rivers in south-eastern Australia

Abstract: Patterns of spatial autocorrelation of biota may reveal much about underlying ecological and biological forces responsible for generating the patterns. Operationally, ecological work and many applied problems (e.g., impact detection, ecosystem health assessment using reference sites) require statistical knowledge of autocorrelation patterns. Here, we report on assemblage-level autocorrelation in the benthic-invertebrate assemblages of riffles in two adjacent, relatively pristine rivers in south-eastern Victori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…DINIZ-FILHO et al (1998) verificaram que o efeito da distância geográfica sobre a fauna de EPT no cerrado do Estado de Goiás foi significativo apenas na estação chuvosa (na estação seca, o efeito não foi significativo). NALLY et al (2006), estudando o efeito da distância entre a fauna de diferentes corredeiras em dois rios australianos, verificaram que em apenas um deles a distância teve um efeito significativo sobre a fauna. Segundo aqueles autores, uma das explicações possíveis para a ausência de autocorrelação espacial em um dos rios estudados foi a ocorrência de impactos de diferentes naturezas e intensidades ao longo deste rio.…”
Section: Discussionunclassified
“…DINIZ-FILHO et al (1998) verificaram que o efeito da distância geográfica sobre a fauna de EPT no cerrado do Estado de Goiás foi significativo apenas na estação chuvosa (na estação seca, o efeito não foi significativo). NALLY et al (2006), estudando o efeito da distância entre a fauna de diferentes corredeiras em dois rios australianos, verificaram que em apenas um deles a distância teve um efeito significativo sobre a fauna. Segundo aqueles autores, uma das explicações possíveis para a ausência de autocorrelação espacial em um dos rios estudados foi a ocorrência de impactos de diferentes naturezas e intensidades ao longo deste rio.…”
Section: Discussionunclassified
“…Moreover, some of the work on stream biota that has specifically assessed the geographic distance over which spatial autocorrelation was evident (Lloyd et al, 2005 would suggest that streams around Zoar Valley are clustered well within such a distance (i.e., *6 km). However, our study focused not on longitudinal stream reaches or connected tributaries, but on distinct laterally adjacent streams among which physical separation precluded the juvenile dispersal that might contribute to spatial autocorrelation among hydrologically connected sites (e.g., Lloyd et al, 2005Lloyd et al, , 2006Mac Nally et al, 2006). In contrast to pure spatial influence, environmental variation was more convincingly associated with benthic community composition in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…At present, an unresolved question in stream ecology regards the degree to which benthic macroinvertebrate communities are structured more by variable environmental conditions versus regional and/or local availability and dispersal of taxa. The latter may yield spatial autocorrelation, wherein physical proximity drives community similarity/dissimilarity among sites independent of environmental conditions (e.g., Parsons et al, 2003;Mac Nally et al, 2006, Heino & Mykra, 2008. Legendre (1993) referred to spatial autocorrelation with the question ''trouble or new paradigm?''…”
Section: Introductionmentioning
confidence: 99%
“…Shannon et al (1996) reported that tributaries on the Colorado River, USA-a regulated desert river-contributed little organic particulate matter to the river. The tributaries may contribute suspended sediment that limits downstream autochthonous production, alters composition of invertebrate drift and changes fish assemblage composition (Shannon et al, 1994(Shannon et al, , 1996Lloyd et al, 2005;Mac Nally et al, 2006). The low levels of organic particulate matter and relatively high levels of suspended sediment from the Colorado tributaries are not surprising given that the catchment is arid.…”
Section: Discussionmentioning
confidence: 99%